Correlation of serum irisin levels with diabetic nephropathy: an exhaustive systematic appraisal and meta-analytical investigation - Deng, Yuan; Shen, Yinhui; Wu, Yuchen; Wen, Min; Wang, Fang (Frontiers in Endocrinology, 2025)
BackgroundDiabetic nephropathy (DN) is a major complication of diabetes, contributing significantly to end - stage renal disease. Irisin, an exercise - induced myokine, has been linked to metabolic disorders, but its relationship with DN remains unclear. This study aims to comprehensively and accurately explore the association between serum irisin levels and DN through a systematic review and meta - analysis.MethodsThe research was conducted following the Meta - analysis of Observational Studies in Epidemiology (MOOSE) guidelines. Multiple electronic databases, including Cochrane Library, Embase, Web of Science, PubMed, China National Knowledge Infrastructure (CNKI), China Biology Medicine disc (CBM), and Wanfang Database, were systematically searched using relevant keywords related to irisin and DN. Studies were included if they were randomized controlled trials (RCTs) or observational studies that stratified Type 2 diabetes mellitus (T2DM) patients based on the presence or absence of DN, measured serum irisin levels in both groups, and provided data in a suitable format. Two independent reviewers performed literature screening, data extraction, and quality assessment. The Jadad scale was used for RCTs, and the Newcastle - Ottawa Scale (NOS) was applied for cohort and case - control studies. Statistical analysis was carried out using RevMan 5.3 software, with heterogeneity evaluated by Q and I² tests, and appropriate models (fixed - effects or random - effects) selected accordingly. INPLASY registration number:202530056.ResultsA total of seven studies, comprising 453 DN patients and 346 non-DN controls, were included in the final meta-analysis. The pooled results demonstrated that serum irisin levels were significantly lower in patients with diabetic nephropathy, particularly those with more advanced stages of albuminuria. Specifically, irisin levels were significantly reduced in patients with microalbuminuria (MD = 30.84, 95% CI: 7.81 to 53.87, I² = 96%) and macroalbuminuria (MD = 30.84, 95% CI: 7.81 to 53.87, I² = 98%) compared to those with normoalbuminuria. Furthermore, a direct comparison between microalbuminuria and macroalbuminuria also revealed significantly lower irisin levels in the latter group (MD = 12.53, 95% CI: 3.46 to 21.59, I² = 89%). In terms of renal function, patients with eGFR < 60 mL/min/1.73 m² exhibited lower irisin concentrations than those with preserved renal function (MD = 3.43, 95% CI: –2.90 to 9.75, I² = 90%), though this difference was not statistically significant. Given the substantial heterogeneity among the included studies, random-effects models were applied for all analyses. Funnel plot assessment showed general symmetry in most comparisons, indicating a low to moderate risk of publication bias, although asymmetry was observed in the microalbuminuria vs. macroalbuminuria subgroup, suggesting potential small-study effects.ConclusionsThis meta-analysis provides evidence for an association between serum irisin levels and DN. Lower serum irisin levels were related to more severe albuminuria and decreased eGFR in T2DM patients. However, considering the limitations of this study, such as potential missing data and methodological differences, further large - scale, multi-center, and high-quality RCTs are needed to validate these findings and elucidate the underlying mechanisms.Systematic review registrationINPLASY.COM, identifier 202530056.